2019
DOI: 10.1111/hdi.12803
|View full text |Cite
|
Sign up to set email alerts
|

Management Strategies for Pain Associated with Arteriovenous Fistula Cannulation: An Integrative Literature Review

Abstract: Patients on maintenance hemodialysis are subjected to mild-to-moderate pain associated with arteriovenous fistula needle insertion. This pain might adversely affect patient compliance with dialysis and quality of life. The aim of this study was to evaluate published research studies on management strategies for pain associated with fistula needle insertion. A review of 35 studies from well-known databases such as CINAHL, ProQuest, and PubMed was conducted. Three strategies of cannulation pain management were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 32 publications
(160 reference statements)
0
17
0
Order By: Relevance
“…In contrast, the underlying cause for the pain cited by the highest percentage of subjects was the dialysis procedure itself (21.6 %). Causes which were attributed to pain may be due to cannulation, steal syndrome, or cramping [28].…”
Section: Presence Site and Causes Of Painmentioning
confidence: 99%
“…In contrast, the underlying cause for the pain cited by the highest percentage of subjects was the dialysis procedure itself (21.6 %). Causes which were attributed to pain may be due to cannulation, steal syndrome, or cramping [28].…”
Section: Presence Site and Causes Of Painmentioning
confidence: 99%
“…The authors suggested that it might reflect a faster systemic uptake of drug because of an increased cardiac output in renal failure [ 34 ]. In addition, reports of toxicity in CKD [ 35 , 36 ] have led to suggestions that the pharmacokinetics of LAs may be altered unfavorably in this condition, although conclusive data in this area are lacking.…”
Section: La Use In Patients With Kidney Diseasementioning
confidence: 99%
“…For patients to receive hemodialysis treatment, a needle must be inserted into the AVF Effect of aromatherapy each time. Considering that patients receive dialysis treatment at least three times a week, patients receive needle interventions quite frequently [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Pain management is one of the most basic nursing interventions. By controlling pain, patients may have increased satisfaction and improved quality of life [6]. Pain management may be achieved by nonpharmacological and pharmacological methods.…”
Section: Introductionmentioning
confidence: 99%